Use of sulfonic acids in dry electrolytes for removing vapor deposition and / or thermal spray coatings from metal surfaces
By using a dry electrolyte containing sulfonic acid on the surface of the workpiece for ion transport removal, the problems of matrix damage and high cost during the coating removal process in the prior art are solved, and an efficient and low-cost coating removal effect is achieved.
Patent Information
- Application Number
- CN202380039859.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-09
- Filing Date
- 2023-05-03
- Publication Date
- 2025-01-03
AI Technical Summary
The prior art tends to cause damage to the substrate surface and high cost when removing coats on worn or inappropriately coated workpieces, and lacks low-cost and reliable methods of peeling the vapor deposition and thermal spray coating.
The dry electrolyte containing sulfonic acid is used to remove the coating from the metal surface through an ion transport method, and porous particles and polyether are used as complexing agents in the conductive liquid to improve removal efficiency and process stability.
Efficient removal of vapor deposition and thermal spray coatings is achieved, avoiding matrix damage, and improving the speed of the removal process and finished product quality while reducing costs.
Smart Images

Figure CN119256123A_ABST
Abstract
Description
[0001] The present invention relates to a method for removing coatings from workpieces such as coated tools and in particular coated cutting tools. The method for removing coatings is used to strip coatings from worn or improperly coated workpieces and thus prepare them for recoating.
[0002] In order to remove coatings from worn and improperly coated workpieces, electrochemical methods are typically used, such as described in WO 2008 / 028311. For this purpose, a coating stripping device is used, which for example comprises a tank for containing a liquid electrolyte, wherein a counter electrode is provided in the tank that can be connected to one pole of a power supply device. In general, the workpieces must be contacted individually in such a way that they are connected to the power supply as anodes and the counter electrode as cathode.
[0003] During use, the tank is filled with electrolyte and the workpiece is immersed in the electrolyte. Between the workpiece and the counter electrode, a predetermined constant voltage is applied, which causes the coating of the workpiece to be removed. The counter electrode surface must be formed and positioned in such a way that the current is distributed as evenly as possible over the surface area of the workpiece whose coating is to be removed, in order to achieve uniform removal of the coating and avoid corrosion of the substrate carrying the coating.
[0004] Another factor influencing the coating removal process is the conductivity of the layer or layers to be removed. One problem that may occur when removing particularly non-conductive layers is damage to the surface of the substrate, so that the substrate is left with statistically distributed notch scars after the coating is removed according to the prior art.
[0005] In US9512539 a method is described how to avoid such notches by starting with a low voltage and continuously increasing the voltage for the decoating process.
[0006] Unfortunately, methods such as those described in WO 2008 / 028311 and US 9512539 involve a high degree of experience and are additionally quite expensive to manufacture.
[0007] There therefore exists a need for an inexpensive yet reliable stripping method for vapor deposited and / or thermally sprayed coatings on metal substrates.
[0008] Stripping is clearly distinguished from polishing. Stripping is a coating removal process which removes the coating from the coated substrate, whereas the minor removal of material known as polishing has the purpose of smoothing the surface. According to DIN 8589, polishing is not a manufacturing process in its own right, but is carried out as polishing grinding, polishing honing or electrolytic polishing.
[0009] In the present context, EP 3 795 722 exclusively relates to polishing. The object of EP 3 795 722 is therefore to develop an improved method for smoothing and polishing metals by ion transport with the aid of free solid bodies.
[0010] The use of sulphonic acid as described in EP3795722 for free solid bodies or particles for polishing metal surfaces by ion transport has the advantages and features explained in EP3795722 and repeated hereinafter.
[0011] A dry electrolyte comprises a set of porous particles that have the ability to hold a given amount of liquid and a given amount of conducting liquid.
[0012] EP 3 795 722 specifically relates to a dry electrolyte comprising porous particles having the ability to retain a given amount of liquid and a given amount of a conductive liquid containing at least one sulfonic acid.
[0013] EP3795722 describes a conductive liquid containing at least one sulfonic acid. Sulfonic acid is composed of the general formula RSO3H, where R can be any organic substituent, either alkyl aromatic, another functional group or a halogen atom. This is the general structure of sulfonic acid:
[0014]
[0015] Preferably, the sulfonic acid used is those with high solubility in water or another selected solvent. In addition, preferably, those sulfonic acids that form soluble salts with the relevant metal. For example, sulfonic acids such as methanesulfonic acid CH3SO3H, trifluorosulfonic acid CF3SO3H, fluorosulfonic acid FSO3H, chlorosulfonic acid ClSO3H, p-toluenesulfonic acid 4-CH3C6H4SO3H and aminosulfonic acid NH2SO3H can be used without limiting the purpose, and they are all represented thereafter.
[0016] Pure sulfonic acid can be used if it is liquid or in solution at the working temperature. The optimal concentration of the sulfonic acid should be determined empirically, since it depends on the chosen sulfonic acid, the solvent and also the parameters of the component to be treated, such as the type of metal, the overall surface and the shape. In solution, the preferred solvent options are water or polar solvents for reasons of conductivity and solubility. Preferably, water is the solvent of choice. Sulfonic acid concentrations of 1% to 70% in the conductive liquid have been shown to be active in this method. Concentrations of 2% to 40% are preferred. These concentrations refer to the final concentration of the conductive liquid in the dry electrolyte, regardless of how the dry electrolyte is prepared.
[0017] Sulfonic acids are strong acids and their handling in liquids or in solutions carries with it a number of handling risks in terms of their use in classical electropolishing. In the liquid state or in solution, these sulfonic acids can produce undesirable attacks on metal surfaces. Therefore, after the use of sulfonic acids in classical electropolishing, an additional neutralization step is usually required.
[0018] However, when it is confined to porous particles, handling becomes easier and the risk of unwanted erosion at the surface is prevented.
[0019] Sulfonic acids with organic waste, such as, but not limiting for purposes of limitation, methanesulfonic acid, trifluorosulfonic acid, and p-toluenesulfonic acid, are much less polar than inorganic acids. Thus, the reduced localized polarity of these sulfonic acids facilitates their migration through the non-polar resin. That is, the smaller sulfonic acid with organic waste, methanesulfonic acid, will benefit from this effect without suffering from steric hindrance.
[0020] In addition, other chemical compounds can be added to the conductive liquid as complexing agents. These agents can capture the formed metal ions and improve the ability to remove metal oxides and salts from the surface.
[0021] Complexing agents with more than one functional group are called chelating agents. By using chelating agents, such as citric acid, EDTA or phosphonates, the effect of capturing and transferring metal ions will be even higher. Due to the metal ions formed on the surface, the agent will have a high affinity and will help to carry the ions to the particles.
[0022] In a preferred embodiment according to EP3795722, the complexing chelating agent is a polyether.
[0023] A polyether is defined as a compound comprising more than one ether group (COC) in its structure, without prejudice to the fact that it may in turn contain other functional groups, such as ester, acid, amino, amide, and the like.
[0024] It was verified that the addition of a polyether to the formulation of the liquid contained in the particles increases the speed of the transfer of ionic metals and thus increases the speed of the polishing process.
[0025] In an even more preferred embodiment according to EP3795722, the polyether is a linear alkyl polyether. In particular, the group of polyethers includes crown ethers and alkyl polyethers. The alkyl polyethers can have different shapes, such as linear, star, branched or comb-shaped. For the electropolishing method, we found that linear alkyl polyethers provide the best results in this method because they are more active at the moment of forming metal complexes.
[0026] In the class of linear alkyl polyether chelating complexing agents, polyethylene glycol or PE is prominent, also known as poly(oxy-1,2-ethinhediyl), poly(ethylene oxide), polyoxyethylene, polyethylene oxide and under trade names such as Carbowax or Macrogol;
[0027] Within the class of linear alkyl polyether chelating complexing agents, polypropylene glycol or PPG is also prominent.
[0028] PEG and PPG are denoted hereafter, where R can be any radical or functional group, preferably H or CH3. The number of repetitions "n" of the repeating unit is an important factor. Metal complexes with polyethers mostly adopt tetrahedral or octahedral conformations, which means that the metal ion is surrounded by four or six oxygen atoms, respectively, which is why the optimal number of repetitions is located around n = 6, as it covers both possibilities.
[0029] In the case of PEG, the preferred molecular weight is 200 Da to 500 Da. Specifically, PEG 300 is most preferred.
[0030] Adding these polymers PEG and PPG to the conductive liquid used to prepare the dry electrolyte containing sulfonic acid, produces a high-speed electropolishing process and a stunning final product. This effect is absolutely not noticeable and is due to a series of cumulative factors: they are soluble in the phase in which they find the sulfonic acid, they have the ability to form complexes with the removed metal ions, they act as phase transfer agents between the liquid retained in the particles and the gel phase of the particles themselves, they are stable to the intensity of the voltage and current to which the process is subjected, and, moreover, they are biologically safe.
[0031] The given amount of conductive liquid that impregnates the porous particles must be high enough to allow a measurable conductivity through the dry electrolyte. Furthermore, this amount must be below the saturation point of the porous particles so that there is no observable free liquid, thus a "dry" electrolyte. Preferably, the amount of conductive liquid is close to but below the saturation point of the porous particles. This amount must be determined empirically, as it depends on the type of sulfonic acid, resin, temperature, solvent and concentration used. For example, for AMBERLITE 252RFH, which has a water retention capacity of 52% to 58%, the optimal amount of conductive liquid consisting of 32% methanesulfonic acid in water ranges from 35% to 50% relative to the absolute dry weight of the resin.
[0032] The material of the porous particles used is preferably based on a sulfonate polymer, which means that it has attached active sulfonic acid groups RSO3H or RSO3-. Preferably, the porous particle sulfonate polymer is based on a styrene copolymer and divinylbenzene. In particular, EP3795722 describes that the porous particles can be ion exchange resins, for example but without limiting purposes, AMBERLITE 252RFH having an ion exchange capacity of 1.7 eql, a density of 1.24 g / ml, a diameter in the range of 0.6-0.8 mm and a water retention capacity in the range of 52% to 58%.
[0033] The synergistic effect between the sulfonic acid groups connected to the polymer and the sulfonic acid groups in the conductive liquid is interesting. It has been found that, in an inconspicuous manner, the fact that these groups are in different states but have the same chemical structure helps the circulation of metal ions from the conductive liquid to the polymer matrix. The direct chemical environment of the metal ions in the solution (complexed by the sulfonate in the solution) and the metal ions in the polymer (complexed by the sulfonate of the polymer) is similar. Therefore, the energy level difference between these states is necessarily very low, which presumably implies a transition state with low energy, which is converted into a higher speed liquid-solid transfer. This has two positive effects on the process, on the one hand, it makes the process faster, and on the other hand, it improves the overall capacity of the resin as a receptor for metal ions, which extends the useful life of the dry electrolyte.
[0034] Thus, when using sulfonic acids in dry electrolytes to polish metal surfaces via ion transport, the sum of these subtle different effects allows for a faster process to achieve stunning results while increasing the useful lifetime of the dry electrolyte.
[0035] An exemplary embodiment as described in EP3795722
[0036] Example 1 in EP3795722
[0037] 1.5 kg of ion exchange resin AMBERLITE 252RFH was mixed and homogenized with 550 ml of a 4% aqueous solution of methanesulfonic acid to prepare a dry electrolyte. This dry electrolyte was used to polish an iron alloy part with a surface area of 5 cm2 having the following composition expressed in %: C (0.17-0.23) Si (0.40) Mn (0.65-0.95) V (0.025) S (0.050) Cr (0.35-0.70) Ni (0.40-0.70) Mo (0.15-0.55) Cu (0.35) Al (0.050). The counter electrode was a titanium-based iridium network. The current used was a positive wave of 50 Hz current at 20 V, which provided an intensity of 0.1 A. The part had a downward / upward movement of about 4 Hz, and the dry electrolyte container was subjected to vibration. After 5 minutes of this procedure, the metal surface acquired amazing properties.
[0038] Example 2 in EP3795722
[0039] 5.3 kg of ion exchange resin AMBERLITE 252RFH was mixed and homogenized with 1950 ml of a 32% methanesulfonic acid solution in water to prepare a dry electrolyte. This dry electrolyte was used to polish an iron alloy component with a surface area of 36 cm2 having the same composition as above. The counter electrode was a titanium-based iridium network. The current used was a positive wave of a 50 Hz current at 30 V. The component had an upward / downward movement of about 4 Hz, and the dry electrolyte container was subjected to vibration. After 10 minutes of this process, the metal surface acquired amazing properties.
[0040] Example 3 in EP3795722
[0041] A solution was prepared with 550 mL of methanesulfonic acid 70%, 160 mL of PEG and 3000 mL of deionized water. This solution was mixed with 6.7 kg of ion exchange resin AMBERLITE 252RFH and homogenized to produce a dry electrolyte. This dry electrolyte was used to polish a 36 cm2 carbon steel part. The counter electrode used was a titanium-based iridium network. The current used was a positive wave of a 50 Hz current at 30 V. The parts had a downward / upward movement of about 4 Hz, and the dry electrolyte container was subjected to vibration. After 5 minutes of this process, the metal surface obtained amazing properties. Summary of the invention
[0042] Returning to the present invention, the inventors surprisingly realised that the polishing method described in EP3795722 can also be effectively used to perform a stripping method.
[0043] The object of the present invention relates to a method for stripping a vapor deposited coating and / or a thermal sprayed coating from a metal surface of a substrate. The core of the present invention is the use of a free solid body containing a sulfonic acid as an electrolyte for ion transport. All aspects described above in relation to EP3795722 can be applied to the stripping method according to the present invention.
[0044] Thus, according to the invention, the sulfonic acid in the free solid body or particles as described above is used to remove vapor deposited and / or thermal sprayed coatings from metal surfaces by ion transport. This can be used in the same manner as described above for polishing. The vapor deposited coating can be, for example, a physical vapor deposition (PVD) coating and / or a chemical vapor deposition (CVD) coating.
[0045] The present invention will now be described in detail based on examples.
[0046] As a first example, a CrAlN-based coating (trade name "FORMERA") was deposited onto a ferroalloy via a cathodic arc. The coating thickness was about 5 μm. A dry electrolyte was prepared by mixing and homogenizing 1.5 kg of an ion exchange resin AMBERLITE 252RFH with 550 ml of a 4% aqueous solution of methanesulfonic acid. This dry electrolyte was used for stripping the ferroalloy substrate. The counter electrode was a titanium-based iridium network. The current used was a positive wave of a 50 Hz current at 20 V, which provided an intensity of 0.1 A. The component had a downward / upward movement of about 4 Hz, and the dry electrolyte container was subjected to vibration. After 30 minutes of this procedure, the coating was completely removed, as shown in FIG. Figure 1 In addition, Figure 1 The surface of the substrate was shown to be slightly rough, suggesting that this process was different from the polishing process.
[0047] As a second example, an AlCrN-based coating (trade name "ALNOVA") was deposited onto carbon steel via a cathodic arc. The thickness of the coating was likewise about 5 μm.
[0048] A solution was prepared with 550 mL of methanesulfonic acid 70%, 160 mL of PEG and 3000 mL of deionized water. This solution was mixed with 6.7 kg of ion exchange resin AMBERLITE 252RFH and homogenized to produce a dry electrolyte. This dry electrolyte was used to strip a carbon steel substrate. The counter electrode used was a titanium-based iridium network. The current used was a positive wave of 50 Hz current at 30 V. The part had a downward / upward movement of about 4 Hz, and the dry electrolyte container was subjected to vibration. After 30 minutes of this process, the coating was completely removed, as shown in FIG. Figure 2 It can be seen in.
[0049] The invention relates to the use of a dry electrolyte for stripping metal surfaces coated by gas phase or thermal spray deposition by ion transport, characterized in that the conductive liquid of the dry electrolyte contains at least a sulfonic acid.
[0050] The porous particles of the dry electrolyte may comprise a sulfonate polymer.
[0051] The porous particles of dry electrolyte may comprise polystyrene-divinylbenzene ion exchange resin.
[0052] The conductive liquid of the dry electrolyte may comprise methanesulfonic acid.
[0053] The concentration of sulfonic acid relative to the solvent may range from 1% to 70%.
[0054] The conductive liquid of the dry electrolyte may include a complexing agent. The complexing agent may include a polyether. The polyether may be a linear alkyl.
[0055] The polyether may comprise or be polyethylene glycol. The polyethylene glycol may have a molecular weight ranging from 200 Da to 500 Da.
[0056] The polyether may be polypropylene glycol.
[0057] The conductive liquid of the dry electrolyte may be a chelating agent.
Claims
1. Use of dry electrolytes for stripping metal surfaces coated by gas phase or thermal spray deposition by ion transport, characterized in that The conductive liquid of the dry electrolyte contains at least sulfonic acid.
2. The use of the dry electrolyte according to claim 1, characterized in that The porous particles of the dry electrolyte comprise a sulfonate polymer.
3. The use of the dry electrolyte according to claim 2, characterized in that The porous particles of the dry electrolyte include polystyrene-divinylbenzene ion exchange resin.
4. Use of a dry electrolyte according to any one of the preceding claims, characterized in that The conductive liquid of the dry electrolyte comprises methanesulfonic acid.
5. Use of the dry electrolyte according to claims 1 and 4, characterized in that The concentration of sulfonic acid relative to the solvent ranges from 1% to 70%.
6. Use of a dry electrolyte according to any one of the preceding claims, characterized in that The conductive liquid of the dry electrolyte contains a complexing agent.
7. The use of the dry electrolyte according to claim 6, characterized in that The complexing agent comprises a polyether.
8. The use of the dry electrolyte according to claim 7, characterized in that The polyether is a linear alkyl group.
9. The use of the dry electrolyte according to claim 8, characterized in that The polyether is polyethylene glycol.
10. Use of the dry electrolyte according to claim 9, characterized in that The polyethylene glycol has a molecular weight ranging from 200 Da to 500 Da.
11. Use of a dry electrolyte according to claim 8, characterised in that The polyether is polypropylene glycol.
12. Use of a dry electrolyte according to any one of the preceding claims, characterized in that The conductive liquid of the dry electrolyte contains a chelating agent.
